2004
DOI: 10.1523/jneurosci.5241-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

β1-Integrins Are Critical for Cerebellar Granule Cell Precursor Proliferation

Abstract: We have previously shown that mice with a CNS restricted knock-out of the integrin ␤1 subunit gene (Itgb1-CNSko mice) have defects in the formation of lamina and folia in the cerebral and cerebellar cortices that are caused by disruption of the cortical marginal zones. Cortical structures in postnatal and adult Itgb1-CNSko animals are also reduced in size, but the mechanism that causes the size defect has remained unclear. We now demonstrate that proliferation of granule cell precursors (GCPs) is severely affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 47 publications
8
115
0
Order By: Relevance
“…Laminin-511 is known to be a major ligand for ␣3␤1 integrin (Kikkawa et al 1998), and previous studies of the deletion of ␣3 integrin have shown severe defects of hair morphogenesis, including altered hair follicle downgrowth. ␤1 integrin has been previously linked to Shh expression in both neural and intestinal tissues (Blaess et al 2004;Jones et al 2006). While prior studies examining the role of ␤1 integrin in hair have focused only on follicular epithelium, not the dermis (Brakebusch et al 2000;Raghavan et al 2000), our present studies suggest that integrins located on dermal cells may play an important role in laminin-511's promotion of hair morphogenesis.…”
Section: Discussionmentioning
confidence: 47%
“…Laminin-511 is known to be a major ligand for ␣3␤1 integrin (Kikkawa et al 1998), and previous studies of the deletion of ␣3 integrin have shown severe defects of hair morphogenesis, including altered hair follicle downgrowth. ␤1 integrin has been previously linked to Shh expression in both neural and intestinal tissues (Blaess et al 2004;Jones et al 2006). While prior studies examining the role of ␤1 integrin in hair have focused only on follicular epithelium, not the dermis (Brakebusch et al 2000;Raghavan et al 2000), our present studies suggest that integrins located on dermal cells may play an important role in laminin-511's promotion of hair morphogenesis.…”
Section: Discussionmentioning
confidence: 47%
“…␤1 integrins were thought to control cell motility in several of these modes of migration (Clegg et al, 2003), but our findings suggest that ␤1 integrins have a much more specific role than previously appreciated. Our previously published data (Graus-Porta et al, 2001;Blaess et al, 2004) provide strong evidence that many of the migratory events that are important for the development of the cerebral and cerebellar cortex progress normally in the absence of ␤1 integrins. Similarly, although studies with function blocking antibodies have suggested that ␤1 integrins control cell motility of neuroblasts in the RMS, for example by controlling leading process extension (Murase and Horwitz, 2002;Emsley and Hagg, 2003), our data now show that ␤1-deficient neuroblasts in the RMS still elaborate extensive leading processes and are able to migrate directionally toward the OB.…”
Section: ␤1 Integrins and Cell Migration In The Cnsmentioning
confidence: 80%
“…In previous experiments, this conditional allele was introduced into a cre line whose expression is driven by the neuronal enhancer element of the nestin gene promoter. This resulted in deletion of the ␤1 integrin gene throughout much of the nervous system and led to severe developmental defects in cerebral cortical lamination and cerebellar foliation (Graus-Porta et al, 2001;Blaess et al, 2004). To study more specifically the functions of ␤1-class integrins in excitatory neurons, we used another cre line whose expression is driven by the emx1 gene promoter by virtue of an internal ribosome entry site element engineered into the emx1 locus (Gorski et al, 2002).…”
Section: Resultsmentioning
confidence: 99%